Battery Control Strategy for Hybrid Power Generation Systems - Junaidi Junaidi; Ayong Hiendro; Yohannes M. Simanjuntak (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Standalone diesel generators (DGs) are widely utilized in remote areas in Indonesia. Some areas use microhydro (MH) systems with DGs backup.  However, highly diesel fuel price makes such systems become uneconomical. This paper introduces hybrid photovoltaic (PV)/MH/ DG/battery systems with a variable charging strategy method to minimize the diesel fuel consumption. The method is applied to control the state of charge (SOC) level of the battery based on its previous level and the demand load condition to optimize the DG operation. The optimal operation shows that the hybrid PV/MH/DG/battery with the variable charging strategy needs less fuel consumption than PV/MH/DG and MH/DG systems.DOI:http://dx.doi.org/10.11591/ijece.v2i4.556